Application of Computer Technology in English Translation Network Teaching - Ren, Junchao (Journal of physics. Conference series, 2020)
The development of modern educational technology and computer network technology will bring translation teaching into a new era, and a new translation teaching model will emerge. Computer network technology is completely suitable for translation teaching, because the type and characteristics of translation teaching determine this applicability. The scientific and artistic nature of translation can enable the learning subject to implement a high degree of self-control and independent learning in the network environment, and actively display creativity and individuality. The teaching subject can also adopt a combination of individualized and collaborative teaching methods to achieve "double "The main teaching mode" means to play the leading role of teachers and the cognitive subject role of students at the same time. The new translation teaching model based on computer network technology will certainly arouse the general attention of the domestic translation teaching circle and be widely used.